Clinical relevance of the differential expression of the glycosyltransferase gene GCNT3 in colon cancer. Issue 1 (January 2015) - González-Vallinas, Margarita; Vargas, Teodoro; Moreno-Rubio, Juan; Molina, Susana; Herranz, Jesús; Cejas, Paloma; Burgos, Emilio; Aguayo, Cristina; Custodio, Ana; Reglero, Guillermo; Feliu, Jaime; Ramírez de Molina, Ana
Abstract Altered glycosylation is considered a universal cancer hallmark. Mucin-type core 2 1, 6-N-acetylglucosaminyltransferase enzyme (C2GnT-M), encoded by the GCNT3 gene, has been reported to be altered in tumours and to possess tumour suppressor properties. In this work, we aimed to determine the possible role of GCNT3 gene expression as prognostic marker in colon cancer. We investigated the differential expression of GCNT3 gene among tumour samples from stage II colon cancer patients by quantitative reverse-transcription polymerase chain reaction (qRT-PCR). Univariate and Multivariate Cox regression analyses were used to determine the correlation between GCNT3 expression and disease-free survival. The risk of relapse in GCNT3 low-expressing cancer patients was significantly higher than that in GCNT3 high-expressing patients in both training (Hazard Ratio (HR) 4.26, p = 0.002) and validation (HR 3.06, p = 0.024) series of patients, and this association was independent of clinical factors. Additionally, qRT-PCR was used to explore the modulation of GCNT3 expression by different antitumour drugs. Three chemotherapeutic agents with different mechanism of action (5-fluorouracil, bortezomib and paclitaxel) significantly induced GCNT3 expression in several cancer cells, being observed the correlation between antitumour action and GCNT3 modulation, whereas this gene was not modulated in cells that do not respond to treatment. Overall, these results indicate that low GCNT3 expression is a promising prognostic biomarker for colon cancer that could be used to identify early-stage colon cancer patients at high risk of relapse. Additionally, our results suggest that this enzyme might also constitute a biomarker to monitor tumour response to chemotherapy in cancer patients.